2018
DOI: 10.1111/ecca.12297
|View full text |Cite
|
Sign up to set email alerts
|

Coase Lecture ‐ The Inverted‐U Relationship Between Credit Access and Productivity Growth

Abstract: We identify two counteracting effects of credit access on productivity growth: on the one hand, better access to credit makes it easier for entrepreneurs to innovate; on the other hand, better credit access allows less efficient incumbent firms to remain longer on the market, thereby discouraging entry of new and potentially more efficient innovators. We first develop a simple model of firm dynamics and innovationbased growth with credit constraints, where the above two counteracting effects generate an invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…Our empirical results suggest a cleansing effect of uncertainty shocks. The literature on cleansing effect demonstrated that during recesssions less productive firms exit from the mar-ket while the most productive survive (Caballero and Hammour, 1994;Foster et al, 2016;Osotimehin and Pappadà, 2016;Aghion et al, 2019). We do not directly measure productivity of firms in our database, but if we proxy it by the return of FDI, our results suggest a cleansing effect too.…”
Section: Resultsmentioning
confidence: 87%
“…Our empirical results suggest a cleansing effect of uncertainty shocks. The literature on cleansing effect demonstrated that during recesssions less productive firms exit from the mar-ket while the most productive survive (Caballero and Hammour, 1994;Foster et al, 2016;Osotimehin and Pappadà, 2016;Aghion et al, 2019). We do not directly measure productivity of firms in our database, but if we proxy it by the return of FDI, our results suggest a cleansing effect too.…”
Section: Resultsmentioning
confidence: 87%
“…Extending the capability design of capital is typically seen to be the basis of substantial employment expansion and firm growth because LTC contributes to faster employment growth, significant welfare, and the stability of the business in two favorable ways-by minimizing rollover challenges for borrowers and by improving the availability of LTC tools. This allows employees and businesses to respond life-cycle risks (Aghion et al, 2019). Consequently, the above discussion leads to the establishment of the following hypothesis:…”
Section: The Nexus Between the Development Of Employment And Long-termentioning
confidence: 96%
“…Botev, Égert, and Jawadi (2019) have examined the fact that organizations that have access to finance are more likely to experience employment growth than those that do not have access to finance. The research conducted by Aghion, Bergeaud, Cette, Lecat, and Maghin (2019) has stated that the relationship between bank credit and employment growth can be determined with the help of credit bureaus that act as an exogenous shock for the supply of credit. This also leads to employment growth of up to 5%, compared to countries where CB has not been introduced yet.…”
Section: Theory Of Long-term Finance (Ltf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term interest rates are generally used to account for financial stability since they encompass the effects derived from the behavior of risk premia and the issuing of government debt (Aghion et al 2012(Aghion et al , 2019Popov, 2017). This financial relationship is controlled through several macroeconomic variables describing the social structure of countries: the Gini Index (GINI) -as a measure of inequality, social expenditure, as well as the levels of education (EDU) and unemployment (UNEM) (Cozzens & Kaplinsky, 2009).…”
Section: Sample and Description Of The Variablesmentioning
confidence: 99%